Pathogenic MAST3 Variants in the STK Domain Are Associated with Epilepsy. Issue 2 (13th July 2021) - Spinelli, Egidio; Christensen, Kyle R.; Bryant, Emily; Schneider, Amy; Rakotomamonjy, Jennifer; Muir, Alison M.; Giannelli, Jessica; Littlejohn, Rebecca O.; Roeder, Elizabeth R.; Schmidt, Berkley; Wilson, William G.; Marco, Elysa J.; et al.
Abstract : Objective: The MAST family of microtubule‐associated serine–threonine kinases (STKs) have distinct expression patterns in the developing and mature human and mouse brain. To date, only MAST1 has been conclusively associated with neurological disease, with de novo variants in individuals with a neurodevelopmental disorder, including a mega corpus callosum. Methods: Using exome sequencing, we identify MAST3 missense variants in individuals with epilepsy. We also assess the effect of these variants on the ability of MAST3 to phosphorylate the target gene product ARPP‐16 in HEK293T cells. Results: We identify de novo missense variants in the STK domain in 11 individuals, including 2 recurrent variants p.G510S (n = 5) and p.G515S (n = 3). All 11 individuals had developmental and epileptic encephalopathy, with 8 having normal development prior to seizure onset at <2 years of age. All patients developed multiple seizure types, 9 of 11 patients had seizures triggered by fever and 9 of 11 patients had drug‐resistant seizures. In vitro analysis of HEK293T cells transfected with MAST3 cDNA carrying a subset of these patient‐specific missense variants demonstrated variable but generally lower expression, with concomitant increased phosphorylation of the MAST3 target, ARPP‐16, compared to wild‐type. These findings suggest the patient‐specific variants may confer MAST3 gain‐of‐function. Moreover, single‐nuclei RNA sequencing and immunohistochemistry shows that MAST3 expression is restricted to excitatory neurons in the cortex late in prenatal development and postnatally. Interpretation: In summary, we describe MAST3 as a novel epilepsy‐associated gene with a potential gain‐of‐function pathogenic mechanism that may be primarily restricted to excitatory neurons in the cortex. ANN NEUROL 2021;90:274–284